Flexible Electronics: Theoretical and Experimental Studies of Epidermal Heat Flux Sensors for Measurements of Core Body Temperature (Adv. Healthcare Mater. 1/2016). Issue 1 (January 2016) - Zhang, Yihui; Chad Webb, Richard; Luo, Hongying; Xue, Yeguang; Kurniawan, Jonas; Cho, Nam Heon; Krishnan, Siddharth; Li, Yuhang; Huang, Yonggang; Rogers, John A.
Abstract : On page 119, J. A. Rogers and co‐workers present theoretical approaches, modeling algorithms, materials, and device designs for the noninvasive measurement of core body temperature by using multiple differential temperature sensors that attach softly and intimately onto the surface of the skin. The image shows the construction of differential temperature sensors using thermally insulating foam as the separation material.